"Friends and companions of Vianna": memory and spiritist identity in dispute in the biography "Vianna de Carvalho, the tribune of Icó" (Tempo e Argumento, 2023)
This article historically problematizes the biography of a great personality of Spiritism in Brazil, entitled “Vianna de Carvalho. O tribuno de Icó” (1999), by Luciano Klein Filho, considering that its publication and the plot of the work are part of a broader project of memorial construction with a view to legitimizing the group to which the author and leader is linked. of the Spiritist Federation of the State of Ceará-FEEC (1990). Exploring the theme of religious disputes in the spiritist environment from the history of the present time, Klein Filho's work is related as a demarcation of a historicity of the origins of the local spiritist movement in the context of the dispute for the affirmation of its identity in front of the competing federative group, organized in the Union of Spiritist Societies of the State of Ceará (1993). In the analysis, the perception emerges that Klein Filho, as an authorized voice to dialogue with the local spiritist past, establishing relationships with great mediums and national spiritists, develops a complex game of legitimations that are capitalized by the FEEC group, in the midst of its alliance with the Brazilian Spiritist Federation. It is concluded that, over the last three decades, the biographical memorial projects have guaranteed greater historical legitimacy to the febian group in Ceará, at the same time that they have stimulated an action taken by the opposing group in the sense of memorialistic investment from other historical landmarks.
Keywords: memory; identity; spiritism; Vianna de Carvalho